ANALISIS EFISIENSI PENGELOLAAN KEUANGAN PADA DISPERINDAGKOP DAN UKM KABUPATEN POHUWATO DENGAN PENDEKATAN COST BENEFIT ANALYSIS - Rahma Nurtiya Matani; Felmi D. Lantowa (Jurnal Akuntansi, Keuangan dan Teknologi Informasi Akuntansi, 2025)
This research aimed to analyze the efficiency of financial management at the Department of Industry, Trade, Cooperatives, and SMEs of Pohuwato Regency using the Cost-Benefit Analysis (CBA) approach, identify effective programs, and provide strategic recommendations. The study employed a quantitative descriptive method, utilizing efficiency ratios, Payback Period, Net Present Value (NPV), and Benefit Cost Ratio (BCR). The results indicated that financial efficiency during 2022-2024 was classified as fairly efficient, with an average of 82.81% However, the CBA results showed that the investment was not economically viable, with a negative NPV, a Payback Period exceeding three years, and a BCR of less than 1. Interviews with SMEs revealed that the assistance provided by the government was beneficial. However, there were weaknesses in administrative aspects and an understanding of regulations. SME operators stated that they had never made payments to the local government and were unaware of tax obligations stipulated in Government Regulation No. 23 of 2018. Keywords : Financial Efficiency, Cost Benefit Analysis, Small And Medium Enterprises, Payback Period, Net Present Value, Benefit Cost Ratio